Aberrant pre-mRNA maturation is caused by LINE insertions into introns of the white gene of Drosophila melanogaster. - Lajoinie, O (1995)
Insertional mutagenesis screens have provided thousands of mutant alleles for analysing genes of varied functions in Drosophila melanogaster. We here document mechanisms of insertional mutagenesis by a LINE element, the I factor, by determining the molecular structure of RNAs produced from two alleles of the white gene of D.melanogaster, wIR1 and wIR6. These alleles result from insertion of the I factor into introns of the gene. We show that sequences present within the element direct aberrant splicing and termination events. When the I factor is inserted within the white first intron it may lead to the use of a cryptic 3' splice site which does not contain the dinucleotide AG. This splicing gives rise to a chimeric messenger RNA whose synthesis is controlled differently in tissues where the mutated gene is expressed. When the I factor is inserted within the white last intron it induces synthesis of truncated mRNAs. These results provide, for the first time, mechanisms for I factor insertional mutagenesis. They are discussed in the more general context of RNA processing in Drosophila and the evolution of eukaryotic gene introns.